The impact of transformational leadership style on the development of human resources management - Zhang, Zezhong (2019)
This study proposes a model of the impact of transformational leadership style on the development of human resources management (HRM). The model collected and analysed questionnaire data of 280 employees from four construction enterprises in China. The results show that transformational leadership style has an important influence on the development of HRM. From the four dimensions (commitment, flexibility, quality and integration) measuring the development of HRM, transformational leadership style has the greatest impact on organisational commitment. The paper also verifies the positive influence of transformational leadership style on organisational integration and fills the gaps in the early literature. Finally, we discuss practical and theoretical implications.